Attitude of inhabitants of Spis Region to refugees and immigrants - Katarína Majcherová (Edukacja Elementarna w Teorii i Praktyce, 2017)
The aim of this s to highlight the attitude of inhabitants towards refugees and immigrants in Spiš region. Refugees come to foreign country not knowing its language and culture. They are often traumatized by events they have gone through. I set attention to create attitudes of regional inhabitants towards immigrants and refugees. Research is focused on inhabitants' awareness and tolerance to this group of people. In conclusion, I indicate forms of helping and possibilities of solving their difficult life situation.